Association between baseline pulse pressure and hospital mortality in non-traumatic subarachnoid hemorrhage patients: a retrospective cohort study - Liu, Jiuling; Wang, Shu; Ji, Lin; Wang, Xiaoqing; Zhao, Hang (Frontiers in Neurology, 2023)
ABSTRACT Background and purpose: Previous studies have described an association between pulse pressure (PP) level and mortality in stroke patients. Evidence of associations between PP level and the risk of mortality remains unknown in non-traumatic subarachnoid hemorrhage (SAH) patients. We aimed to explore the relationship between the baseline PP level and hospital mortality. Methods: This cohort study of 693 non-traumatic SAH adults used Medical Information Mart for Intensive Care (MIMIC-IV) data from 2008-2019 admissions to Intensive Care Unit (ICU). PP level was initially assessed upon ICU admission. The endpoint of the study was in-hospital mortality. Cox proportional hazards models were utilized to analyze the association between baseline PP level and hospital mortality. Restricted Cubic Splines (RCS) analysis was utilized to determine the relationship curve between hospital mortality and PP level and examine the threshold saturation effect. We further applied Kaplan-Meier survival curve analysis to examine the consistency of these correlations. The interaction test was used to identify subgroups with differences. Results: The mean age of the study population was 58.8±14.6 years, and 304 (43.9%) of participants were female. When baseline PP level was assessed in quartiles, compared to the reference group (Q1 ≤56mmHg), the adjusted hazard ratio (HR) in Q2 (57-68mmHg), Q3(69-82mmHg), Q4 (≥ 83mmHg) were 0.55 (95% CI: 0.33-0.93, p = 0.026), 0.99 (95% CI, 0.62-1.59, p = 0.966), and 0.99 (95% CI: 0.62-1.59, p = 0.954), respectively. In the threshold analysis, for every 5 mmHg increase in PP level, there was an 18.2% decrease in hospital mortality (adjusted HR, 0.818; 95% CI, 0.738-0.907; P = 0.0001) in those with PP level 60mmHg, and a 7.7% increase in hospital mortality (adjusted HR, 1.077; 95% CI, 1.018-1.139; P = 0.0096) in those with PP level 60mmHg or higher. Conclusion: For patients with non-traumatic SAH, the association between baseline PP and risk of hospital mortality was non-linear, with an inflection point at 60mmHg and a minimal risk at 57 to 68 mmHg (Q 2) of baseline PP level.